Pathogenesis of thyroid-associated ophthalmopathy: does autoimmunity against calsequestrin and collagen XIII play a role? - Lahooti, Hooshang (Dove Medical Press, 2010)
Thyroid-associated ophthalmopathy (TAO), or thyroid eye disease, is a complex inflammatory disorder of the eye that, as its name implies, is associated with thyroid disease. TAO can be divided into three subtypes: ocular myopathy, congestive myopathy and mixed congestive and myopathic ophthalmopathy. Although the precise pathophysiology of TAO remains unclear it is likely to reflect an autoimmune reaction involving sensitized T-cells and autoantibodies directed against a thyroid and orbital tissue shared antigen. One well studied candidate in this immune reaction is the thyroid-stimulating hormone receptor (TSH-r), expressed in the orbital fibroblast and pre adipocyte. In our studies of TAO, we have investigated the nature and significance of antibodies targeting other eye muscle and orbital connective tissue (OCT) antigens. Our findings suggest that autoimmunity against the eye muscle antigen calsequestrin and the OCT antigen collagen XIII plays a role in the pathogenesis of TAO. We propose that ocular myopathy and chronic eyelid retraction are due to autoimmunity against skeletal muscle calsequestrin in the extraocular and eyelid muscles, respectively. This may be initiated in the thyroid where calsequestrin expression is upregulated, possibly due to a stimulatory effect of TSH-r antibodies. We also propose that congestive ophthalmopathy results from a reaction against the TSH-r or collagen XIII in orbital fibroblast cell membranes. Further insight into the role of eye muscle and OCT antigens in the pathogenesis of TAO may allow for the development of new therapies to treat the eye disorder and reduce patient morbidity.